A rapid screening of histamine concentration in fish fillet by direct analysis in real time mass spectrometry (DART-MS). (May 2017) - Nei, Daisuke; Nakamura, Nobutaka; Ishihara, Kenji; Kimura, Meiko; Satomi, Masataka
Abstract: Histamine is a biogenic amine causing scombroid foodborne poisoning. A rapid determination of the amine is effective in preventing the distribution of histamine-accumulated foods to market. Conventional methods for the determination of histamine concentration in foods include analyses by high performance liquid chromatography (HPLC). The present study tried to utilize a direct analysis in real-time ionization coupled to mass spectrometer (DART-MS) to estimate the histamine concentration in fish filets as an alternative to HPLC. The DART-MS responses to histamine and 1, 8-diaminooctane as an internal standard were highly dependent on heater temperature; the highest responses were obtained at 400 °C. Histamine was spiked from 16.3 mg/kg to 407.0 mg/kg in tuna and yellowtail filets to obtain contaminated samples. The contaminated samples were homogenized with 0.1 mM EDTA containing 1, 8-diaminooctane. The filtrates of the suspension were analyzed by DART-MS, and peak areas corresponding to the histamine and internal standard were obtained. The ratios of the histamine peaks to the internal standard peaks increased with higher histamine concentrations in the fish filets. The high linearity between the histamine concentrations and peak area ratios and the determination coefficient was more than 0.95. The results suggested that DART-MS is an attractive tool as a rapid screening method for determining histamine concentrations in fish filets. Highlights: DART-MS was applied for screening of histamine in fish fillets. The peak of histamine was observed by DART-MS analyses of fish samples. Peak areas were linearly increased with histamine concentration. A substantial matrix effect may have resulted in overestimated histamine values.